Forensic Accounting, Preventing And Detecting Fraud: A Systematic Literature - Kinanti, Kania Putri; Amalia, Firda Ayu; Widyastuti, Aviani; Wicaksono, Agung Prasetyo Nugroho (Journal of Accounting and Finance Management, 2024)
This research was conducted to map and describe research related to forensic accounting in preventing and detecting fraud. A sample of 31 Scopus-indexed literature was selected using the PRISMA method. A selection of 51 pieces of literature was then analyzed using the SLR method and assisted by VOSViewer software. The results of this research show that literature with the keyword Fraud is the literature that is most related to the keyword forensic accounting, thus indicating that forensic accounting research related to Fraud research is carried out more often than other topics.